Christmas in Connecticut [videorecording (DVD)] - Godfrey, Peter, 1899-1970; Stanwyck, Barbara, 1907-1990; Morgan, Dennis, 1908-1994; Greenstreet, Sydney (Turner classic movies., 2005)
A famous food writer lies about living on a farm, raising her children and being a good cook. In reality she is an unmarried New Yorker who can't boil an egg. When her publisher announces that she will host Christmas for an heroic sailor (and for him), her job is on the line.